Real‐world analysis of main clinical outcomes in patients with polycythemia vera treated with ruxolitinib or best available therapy after developing resistance/intolerance to hydroxyurea. Issue 13 (13th April 2022) - Alvarez‐Larrán, Alberto; Garrote, Marta; Ferrer‐Marín, Francisca; Pérez‐Encinas, Manuel; Mata‐Vazquez, M. Isabel; Bellosillo, Beatriz; Arellano‐Rodrigo, Eduardo; Gómez, Montse; García, Regina; García‐Gutiérrez, Valentín; Gasior, Mercedes; Cuevas, Beatriz; et al.
Abstract : Background: Ruxolitinib is approved for patients with polycythemia vera (PV) who are resistant/intolerant to hydroxyurea, but its impact on preventing thrombosis or disease‐progression is unknown. Methods: A retrospective, real‐world analysis was performed on the outcomes of 377 patients with resistance/intolerance to hydroxyurea from the Spanish Registry of Polycythemia Vera according to subsequent treatment with ruxolitinib (n = 105) or the best available therapy (BAT; n = 272). Survival probabilities and rates of thrombosis, hemorrhage, acute myeloid leukemia, myelofibrosis, and second primary cancers were calculated according to treatment. To minimize biases in treatment allocation, all results were adjusted by a propensity score for receiving ruxolitinib or BAT. Results: Patients receiving ruxolitinib had a significantly lower rate of arterial thrombosis than those on BAT (0.4% vs 2.3% per year; P = .03), and this persisted as a trend after adjustment for the propensity to have received the drug (incidence rate ratio, 0.18; 95% confidence interval, 0.02‐1.3; P = .09). There were no significant differences in the rates of venous thrombosis (0.8% and 1.1% for ruxolitinib and BAT, respectively; P = .7) and major bleeding (0.8% and 0.9%, respectively; P = .9). Ruxolitinib exposure was not associated with a higher rate of second primary cancers, including all types of neoplasia, noncutaneous cancers, and nonmelanoma skin cancers. After a median follow‐up of 3.5 years, there were no differences in survival or progression to acute leukemia or myelofibrosis between the 2 groups. Conclusions: The results suggest that ruxolitinib treatment for PV patients with resistance/intolerance to hydroxyurea may reduce the incidence of arterial thrombosis. Lay Summary: Ruxolitinib is better than other available therapies in achieving hematocrit control and symptom relief in patients with polycythemia vera who are resistant/intolerant to hydroxyurea, but we still do not know whether ruxolitinib provides an additional benefit in preventing thrombosis or disease progression. We retrospectively studied the outcomes of 377 patients with resistance/intolerance to hydroxyurea from the Spanish Registry of Polycythemia Vera according to whether they subsequently received ruxolitinib (n = 105) or the best available therapy (n = 272). Our findings suggest that ruxolitinib could reduce the incidence of arterial thrombosis, but a disease‐modifying effect could not be demonstrated for ruxolitinib in this patient population. Abstract : Ruxolitinib may reduce the incidence of arterial thrombosis in patients with polycythemia vera resistant/intolerant to hydroxyurea.